Struktur dan Perkembangan Motif Pinto Aceh - T Azizi; Asril Asril (Pascasarjana Institut Seni Indonesia Padang Panjang, 2018)
Pinto aceh motif is one of crafts that has existed as the ornament and rapidly evolves in Aceh. Pinto aceh motif is formed of the flora and fauna elements sourced from the wealth of Aceh sea and the geometrical motif element. Overall, the pattern of pinto aceh motif is symmetrical. The creation of pinto aceh motif evolves by experiencing the stylization of basic form into creation one. Its usage is not only on brooch and pendant but also on various textile media, wood, concrete, and metal. This article aims at discussing the structure and development of pinto aceh motif until becoming the ornaments. This study used the descriptive qualitative method. The data collection was conducted through observation, interview, and photo documentation to analyze the details of the structure and development of pinto aceh motif. The structure of pinto aceh motif was analyzed by using the theory of form and structure; while its development was analyzed by using the theory of creativity. The research results show that pinto aceh motif is made in the symmetrical pattern, its stuffing is sourced from the flora and fauna, its basic frame is inspired from pinto khop building, and its development has been widely applied on various crafts. Therefore its structure has been largely created.Keywords: structure, pinto aceh motif, development, flora and fauna, symmetricalAbstrakMotif pinto aceh merupakan salah satu seni kriya yang telah berwujud menjadi ornamen yang berkembang pesat di Aceh. Motif pinto aceh terbentuk dari unsur flora, fauna yang bersumber dari kekayaan laut Aceh, dan unsur motif geometris. Secara keseluruhan pola motif pinto aceh adalah simetris. Penciptaan motif pinto aceh berkembang mengalami stilisasi dari bentuk dasar menjadi kreasi. Penggunaannya tidak hanya pada bros dan liontin saja, namun juga pada berbagai media tekstil, kayu, beton, dan logam. Artikel ini bertujuan membahas struktur dan perkembangan motif pinto aceh hingga menjadi ornamen. Kajian ini menggunakan metode kualitatif bersifat deskriptif. Pengumpulan data dilakuan melalui pengamatan, wawancara, dan dokumentasi foto untuk menelaah detail struktur dan perkembangan motif pinto aceh. Struktur motif pinto aceh dianalisis dengan teori bentuk dan struktur, sedangkan perkembangannya dianalisis dengan teori kreativitas. Hasil penelitian menunjukkan bahwa, motif pinto aceh dibuat dalam pola simetris, isiannya bersumber dari flora dan fauna, kerangka dasar terispirasi dari bangunan pinto khop, dan perkembangan motif pinto aceh telah banyak diterapkan pada berbagai hasil kerajinan, sehingga strukturnya telah banyak dikreasikan.